Big bug : &, On the map - Moore, Jenny, 1975-; Frescura, Camilla; Moore, Jenny, 1975-; Moore, Jenny, 1975- (Minneapolis : Lerner Publications, 2025)
Bugs debate who is biggest and an adventurous squirrel looks for buried treasure.
Ages 4-8.
Grades K-1.
Keywords: Insects -- Juvenile fiction; Squirrels -- Juvenile fiction; Treasure troves -- Juvenile fiction; Insects -- Fiction; Squirrels -- Fiction; Buried treasure -- Fiction; Readers; Readers (Publications); Picture books